Effect of Sand Type and PVA Fiber Content on the Properties of Metakaolin Based Engineered Geopolymer Composites. Issue 12 (December 2021) - AbuFarsakh, Ruwa; Arce, Gabriel; Hassan, Marwa; Huang, Oscar; Radovic, Miladin; Rupnow, Tyson; Mohammad, Louay N.; Sukhishvili, Svetlana
This study investigates the mechanical and physical properties of engineered geopolymer composites (EGCs) consisting of metakaolin (MK) based geopolymer (GP) binder, microsilica sand (MS) or river sand (RS), and polyvinyl alcohol (PVA) fiber. Plain GP matrices and fiber-reinforced composites were studied. Aspects of the material composition evaluated here included binder composition, aggregate type, and fiber content. Compressive strength test results revealed that GP mortars presented greater compressive strength than pure GP binders. Moreover, the addition of PVA fibers produced an important increment in compressive strength while increases in fiber content generally enhanced compressive strength. MS composites tended to produce higher compressive strength than RS composites. While exhibiting low densities (i.e., 1.80–1.94 g/cm 3 ), the composite materials evaluated exceeded the compressive strength of regular concrete (i.e., 30 MPa). Furthermore, the best performing composite presented a compressive strength of 57.5 MPa, thus falling in the category of high-strength concrete. The EGC-like tensile pseudo strain-hardening (PSH) behavior of MK-based GP composites was confirmed by a uniaxial tensile test with MS-composites exhibiting greater tensile strength and ductility compared with RS composites; yet, robust PSH behavior was not achieved mainly because of a lack of proper fiber dispersion. Scanning electron microscopy (SEM) revealed unreacted metakaolin particles in some areas within the geopolymer gel of both GP binders evaluated in this study, suggesting incomplete geopolymerization in the binder. Furthermore, energy dispersive X-ray spectroscopy (EDS) microchemical analysis of a geopolymer gel encountered close agreement between the target composition of the GP binders produced and the actual chemical composition encountered in the specimens evaluated.